A fluorescent probe emitting in near-infrared region for sensitive and selective detection of biothiols in both solution and living cells. Issue 52 (30th December 2015) - Chen, Wenqiang; Luo, Hongchen; Liu, Xingjiang; Qi, Fengpei; Yang, Dalei; Song, Xiangzhi
Graphical abstract: A fluorescent probe with an emission in near-infrared region was developed for sensitive and selective detection of biothiols. Moreover, this probe was successfully applied to visualize biothiols in living cells. Abstract: A fluorescent probe, 1, 4-diethyl-7-(3-pyridin-2-yl-acroyloyl)-1, 2, 3, 4-tetrahydro-5-oxa-1, 4-diazaanthracen-6-one (probe1 ), with an emission in near-infrared region was developed for sensitive and selective detection of biothiols. Probe1 is essentially non-fluorescent due to the strong intramolecular charge transfer (ICT) from the electron-donating tetrahydroquinoxaline moiety to the electron-withdrawing pyridine group. Upon the treatment with biothiols, the conjugation system was broken via Michael addition reaction between biothiols and α, β-unsaturated ketone, which inhibited the ICT process and resulted in a remarkable fluorescence enhancement with an emission maximum at 660 nm. Moreover, probe1 was successfully applied to image intracellular thiols in living cells.